PUBLIC EDUCATION AND AWARENESS FOR DISASTER (PEAD): IDENTIFICATION OF THE IMPACT OF THE COVID-19 PANDEMION THE EVENT OF DECREASED SELF CARE AS AN EFFORT TO INCREASE PEAD IN THE COMMUNITY OF THE CITY OF BANJARMASIN - Mohtar, M Sobirin; Rahman, Subhannur (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2023)
Introduction:This pandemic disaster significantly reduced the community's self-care ability related to physical function and vitality and the lack of mitigation by using their own capacity. Based on this, it was emphasized how important it is to identify early on the impact of the COVID-19 pandemic on Decreased Self-Care events, so that it is necessary to implement Public Education and Awareness for Disaster (PEAD) in overcoming these impacts.Methods: Type Analytical survey with cross sectional design. The sample is people in the city of Banjarmasin who are affected by the pandemic and measured Decreased Self-Care through the DSCAI-90 parameter. The statistical test used is Kolmogorov-Smirnov.Results:The average Decreased Self-care of respondents affected by the post-covid-19 disaster is that they lack self-care or require assistance (62.4%). Based on the statistical test obtained a significance value of 0.003.Conclusions:There is a relationship between identification of the impact of the COVID-19 pandemic disaster on the incidence of decreased self-care. One form of Public Education and Awareness for Disaster that is given to the community is the provision of education about nursing care after a pandemic disaster through virtual care.